2020
DOI: 10.1097/ta.0000000000002802
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ride sharing service availability and decreased alcohol-related motor vehicle collision incidence and fatality

Abstract: BACKGROUND Alcohol-related motor vehicle collisions (AR-MVCs) account for ~30% of all US traffic fatalities. Ride-sharing services (RSS) have existed since 2010, but few studies to date have investigated their impact on AR-MVCs. We hypothesized that the availability of RSS would be correlated with a decrease in AR-MVCs at an urban Level I trauma center. METHODS A retrospective chart review was conducted of all AR-MVC trauma activations at a Level I trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Lacking a control condition did not allow us to test whether intoxicated decision strategies align with sober decision strategies which could inform interventions before a drinking episode. Early adulthood has the highest rates of AID, but middle-to-older adults may have differing views on ride services and distinct patterns of acute alcohol tolerance which could better inform interventions among an older age group (Friedman et al, 2020;Conner et al, 2021). Although we were able to classify most individuals into either compensatory or non-compensatory strategy use, future research should determine whether there are other decision making strategies being used or the absence of identifiable strategies among unclassified individuals.…”
Section: Limitationsmentioning
confidence: 86%
See 2 more Smart Citations
“…Lacking a control condition did not allow us to test whether intoxicated decision strategies align with sober decision strategies which could inform interventions before a drinking episode. Early adulthood has the highest rates of AID, but middle-to-older adults may have differing views on ride services and distinct patterns of acute alcohol tolerance which could better inform interventions among an older age group (Friedman et al, 2020;Conner et al, 2021). Although we were able to classify most individuals into either compensatory or non-compensatory strategy use, future research should determine whether there are other decision making strategies being used or the absence of identifiable strategies among unclassified individuals.…”
Section: Limitationsmentioning
confidence: 86%
“…Lacking a placebo condition did not allow us to test whether intoxicated decision strategies align with sober decision strategies which could inform interventions before a drinking episode. Early adulthood has the highest rates of AID, but middle-to-older adults may have differing views on ride services and distinct patterns of acute alcohol tolerance which could better inform interventions among an older age group (Conner et al, 2021; Friedman et al, 2020). We also did not collect or assess whether individuals had a history of DWI or being stopped in suspicion of impaired driving.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frontal airbags, which have been shown in trials to reduce the incidence of brain injury in frontal crashes, became a requirement for all passenger vehicles in the United States in 1999 21. Ridesharing applications such as Uber and Lyft became prevalent in most major cities in the United States between 2011 and 2014, and studies have suggested that they may reduce alcohol-related motor vehicle accidents 22,23. This premise is supported by data from the National Highway Traffic Safety Administration's roadside survey, which shows a decreasing trend in alcohol use among drivers from 1996 to 2014 24.…”
Section: Discussionmentioning
confidence: 96%
“…(2020) showed that the increase in population density, number of registered vehicles, number of holidays, average temperature, percentage of heavy vehicles and percentage of professionals' earners in a region increase in the number of occurrences of this type of incident. The study by Friedman et al (2020) showed that the incidence of alcohol-related motor vehicle accidents attended at the study trauma center decreased after the introduction of ride-sharing services, showing that this can be one of the solutions for preventing this type of accident.…”
Section: Logical Reasoning Of Shares To Be Usedmentioning
confidence: 98%